2016
DOI: 10.30539/iraqijvm.v40i1.142
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of E.coli O157:H7 in fecal and urine samples of cattle

Abstract:      This study was designed to isolate of Enterohaemoragic E.coli O157:H7 from feces and urine in cattle. 175 samples (80 fecal and 95 urine) were collected to isolate EHEC O157:H7 during the period from March to June 2014 from Al- Hindia slaughter house from local breeding cattle, aged between 1-2 years and over 2 years, and the samples were subjected to culture on specific media Cefixime Tellurit- Sorbitol MacConkey agar at 37 ˚C for 18-24 hrs. then the isolates were identified by biochemical tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…This is higher than the study done in Debre-Birhan, Ethiopia (0.81%) [ 19 ], Hawassa, Ethiopia (4.7%) [ 34 ], Jimma, Ethiopia (7.3%) [ 48 ], Addis Ababa Municipal Abattoir, Ethiopia (6.4%) [ 49 ], Debre-Zeit, Ethiopia (7%) [ 50 ], Sudan (8%) [ 45 ], and Nigeria (0.2%) [ 51 ]. However, it is lower than the study reported in Iraqi (91.25%) [ 52 ], and Mexico (22.03%) [ 39 ]. These variations among different studies could be attributed to differences in geographical area, and the type of samples taken since recto-anal mucosal swab sample is more sensitive than fecal sampling for determining the prevalence of STEC O157:H7 in ruminant animals [ 6 ].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This is higher than the study done in Debre-Birhan, Ethiopia (0.81%) [ 19 ], Hawassa, Ethiopia (4.7%) [ 34 ], Jimma, Ethiopia (7.3%) [ 48 ], Addis Ababa Municipal Abattoir, Ethiopia (6.4%) [ 49 ], Debre-Zeit, Ethiopia (7%) [ 50 ], Sudan (8%) [ 45 ], and Nigeria (0.2%) [ 51 ]. However, it is lower than the study reported in Iraqi (91.25%) [ 52 ], and Mexico (22.03%) [ 39 ]. These variations among different studies could be attributed to differences in geographical area, and the type of samples taken since recto-anal mucosal swab sample is more sensitive than fecal sampling for determining the prevalence of STEC O157:H7 in ruminant animals [ 6 ].…”
Section: Discussioncontrasting
confidence: 63%
“…Sudan (8%) [45], and Nigeria (0.2%) [51]. However, it is lower than the study reported in Iraqi (91.25%) [52], and Mexico (22.03%) [39]. These variations among different studies could be attributed to differences in geographical area, and the type of samples taken since recto-anal mucosal swab sample is more sensitive than fecal sampling for determining the prevalence of STEC O157:H7 in ruminant animals [6].…”
Section: Plos Onementioning
confidence: 93%
“…Food-borne diarrhea, bloody diarrhea, and hemolytic uremic syndrome each account for around 4% of all infection cases in children. (Al-Rudha, 2016). Urinary tract infections occurring by E. coli O157:H7 are one of the most important illnesses in babies and children, and they are one of the leading causes of renal failure and mortality in patients (Al-Iraqi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to infecting adults,as well as these organisms are also responsible for various outbreaks in animals, poultry, and humans around the world. These organisms cause food-borne diarrhea, urinary tract infection, bloody diarrhea, and hemolytic uremic syndrome, which occur with an average of 4% of infections in women and children (Khudhir et al, 2022).One of the most serious illnesses in babies and children which induce renal failure or result in patient death is urinary tract infection brought on by E. coli O157:H7 (Al-Rudha, 2016).…”
mentioning
confidence: 99%